Anomalous Origin of Left Coronary Artery From the Pulmonary Artery and Mitral Valve Cleft: A Rare Combination. (December 2020) - Zhang, Yanting; Wang, Bin; Zhang, Li; Wang, Jing; Li, Yuman; Xie, Mingxing
Abstract : Supplemental Digital Content is available in the text.